Isolated orbital roof blow-in fracture. (December 2017) - Rountree, Kaitlyn M.; Blase, John J.
Abstract: We report a rare case of a right orbital roof blow-in fracture in a 40-year-old male with concomitant basal skull fracture and intracranial hemorrhage after a fall backward. Trauma, neurosurgery, ophthalmology, and maxillofacial surgery consultations were obtained. Conservative, non-surgical management was recommended for all injuries, and outpatient follow up for orbital fracture with no surgery offered.